Kaizen technologies in natural and economic systems management: approaches to economic and mathematical modeling (Economics and region, 2019)
The mathematical model of a territorial community management based on a multi-sectoral model of a national economy and Kaizen strategy has been built. According to the modelling a united territorial community is a "closed system". This allows to determine the internal functioning potential to assess the possibilities of self-financing and break-even point. In the multi-sectoral model for a territorial community, we assume that the elements of this complex system are the basic factors of production, namely, land, labour, capital, entrepreneurial skills and information. It has been found out that effective management of territorial community’s internal potential allows to assess its internal economic security rate based on autonomy and self-sufficiency. It has been proved that Kaizen strategies cause effective organization, control and managerial influence on a complex system like a territorial community in the context of its dynamic development.
Keywords: united territorial community; sustainable development; innovative technologies; natural and economic systems; management